Understanding repeaters in an ESL writing course : a case study among pre-sessional students - Rosnani Kassim (Kulliyyah of Education, International Islamic University Malaysia, 2016)
Learning how to write in a second language (ESL) is one of the most challenging aspects of second language learning (Hyland, 2003). In ESL writing classes or courses, we often observe students struggling to learn the writing skills. Some students even fail the same writing course repeatedly. Why do these students fail? This study sought to explore the experience of these students who were referred to as repeaters in learning writing in a pre-sessional English course at the International Islamic University Malaysia (IIUM). In doing so, the study intended to elicit the perceptions of the repeaters in learning writing as well as to understand their difficulties, coping mechanisms and needs in learning ESL writing. This is a case study involving 5 international undergraduate students studying in the English Level 6 course at a language centre in IIUM. These students had failed the same writing course at least twice. The main data collection technique was semi-structured interviews with the repeaters and triangulated with the data from the students' diary entries and also information gathered from semi-structured interviews with their writing instructors. The data were transcribed, analysed and the emerging themes were categorised and discussed. The findings revealed that the repeaters generally had negative perceptions and unpleasant experience towards learning writing. Their problems, coping mechanisms and needs were also highlighted. These finding led to the conceptualization of a model on the main Dimensions in Learning ESL Writing for Repeaters which can be a valuable guide to understanding the repeaters in order to provide more conducive and successful learning and teaching environment for them to learn writing. This study has crucial implications for writing instructors and curriculum developer to create more effective and successful writing courses especially for repeaters. Moreover, it would also provide input for the IIUM policy makers especially in reviewing existing policies or formulating new policies so that the predicament of the repeaters are addressed.